Lymphocyte Updates (IntechOpen, 2023)
This book represents a synergic effort of an international team of specialists in immunology to expand the scientific achievements in the field of lymphocytes. It offers important and specific updated information to researchers, students, teachers, and medical professionals. Moreover, considering the remarkable dynamics of immunology and immunotherapy, this book "Lymphocyte Updates - Cancer, Autoimmunity, and Infection" aims to represent a significant source of concise scientific data and advancement of knowledge in this field. The chapters offer new insights into the latest scientific progress on lymphocyte roles in protective immunity, as well as their involvement in pathogenesis of various disorders.